Pengaruh GCG dan Leverage terhadap Nilai Perusahaan melalui ICD sebagai Variabel Intervening pada Indeks LQ30 Bursa Efek Indonesia Tahun 2022–2024 - Elly Nazathul Rohmah; Erna Puspita; Diah Nurdiwaty (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2026)
This research is motivated by problems that arise in companies listed on the LQ30 index on the Indonesia Stock Exchange (IDX) in 2022-2024. These include: poor company value will be viewed negatively by potential investors; lack of transparent GCG and accountability in company management will impact company value; high leverage will prevent company value from increasing; and poor ICD will impact its intellectual assets, which can affect investor perceptions of company value. The study aims to determine the factors that influence company value. The dependent variable in this study is company value; the independent variables are GCG and Leverage; and the intervening variable is ICD. Data were obtained from companies listed on the LQ30 index in 2022-2024 on the Indonesia Stock Exchange. The research method used is a quantitative approach with causal research techniques. The population in this study is 30 companies listed on the LQ30 index on the Indonesia Stock Exchange for the period 2022-2024; and the sample size is 20 companies meeting certain criteria. The techniques used are path analysis, classical assumption test, R2 coefficient of determination test, and hypothesis test (t-test and F-test). The results of the partial test study indicate that the GCG Leverage and ICD variables partially have a significant effect on Company Value. The results of the partial test study on the intervening variable indicate that the GCG and Leverage variables partially have a significant effect on ICD. Based on the results of the path analysis, it is known that indirectly, GCG through ICD has a significant effect on company value and indirectly, leverage through ICD has a significant effect on company value. The results of this study are expected to be used as a reference for other companies listed on the IDX to pay more attention to financial ratios to increase company value.